Environmental Issues and Major Powers - صبيحي شهيناز (Milev Journal of Research and Studies, 2019)
This study attempts to analyze The nature of the dispute between the major powers in environmental matters by analyzing the strategic calculations of major powers and try out the Least bill and the greatest possible gains, This major powers trying to use negotiations and treaties on environmental issues as a way to expand their areas of influence and trying to adapt to this situation, rather than collapse. The major powers have transformed the environmental issues You seek to protect the earth from environmental degradation is a priority for the negotiations and meetings To file as a bargaining strategy in the conflict on the energy resources in the profit and loss accounts for the states, So that the negotiations Turned from the global interest to the national interest and the geo-strategic accounts balances between nations.